2020
DOI: 10.1021/acsanm.9b02453
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition and Patterning of 15–185 nm Thick Al2O3 Films with Microplasma Arrays for Low-Temperature Growth and Sub-300 nm Lateral Feature Resolution

Abstract: Aluminum oxide (Al2O3) films 15–185 nm in thickness have been grown on Si(100) by a modified atomic layer deposition (ALD) process in which the oxygen precursor is dissociated by a 50 × 20 array of microcavity plasmas. The unique characteristics of microplasmas with respect to electron temperature, specific power loading, and operation at elevated pressures enable the efficient dissociation and excitation of strongly bound precursors such as O2. Microplasma arrays are also sufficiently compact so as to be situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recently, Kim et al [ 24 ] demonstrated that the introduction of microplasma arrays into atomic layer deposition (ALD) systems reduces the reliance on substrate temperature, thereby allowing dielectric films of high electrical and optical quality to be deposited at temperatures considerably lower than those normally required. Specifically, microplasma arrays provide a compact means for dissociating strongly bound precursors such as O and NO but, of equal importance, also produce radicals and excited species capable of favorably altering the chemistry at the interface between the substrate and growing film so as to permit the substrate temperature to be reduced significantly.…”
Section: Deep-uv Bandpass Filters and Mirrors Fabricated By Microplas...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kim et al [ 24 ] demonstrated that the introduction of microplasma arrays into atomic layer deposition (ALD) systems reduces the reliance on substrate temperature, thereby allowing dielectric films of high electrical and optical quality to be deposited at temperatures considerably lower than those normally required. Specifically, microplasma arrays provide a compact means for dissociating strongly bound precursors such as O and NO but, of equal importance, also produce radicals and excited species capable of favorably altering the chemistry at the interface between the substrate and growing film so as to permit the substrate temperature to be reduced significantly.…”
Section: Deep-uv Bandpass Filters and Mirrors Fabricated By Microplas...mentioning
confidence: 99%
“…Experiments conducted at the University of Illinois have deposited both Al O and Ga O films at substrate temperatures of 50 C and room temperature, respectively, by this process known as microplasma-assisted ALD (MALD). Aluminum oxide films 30 nm in thickness, for example, were characterized electrically in metal-oxide/semiconductor capacitors (MOSCAPs) and found to have values of electrical breakdown strength ( ) above 4.1 MV/cm [ 24 ]. Another asset of microplasma arrays for film deposition, growth, and etching is their compact size, which allows for multiple arrays to be situated within the reactor and in proximity to one or more substrates.…”
Section: Deep-uv Bandpass Filters and Mirrors Fabricated By Microplas...mentioning
confidence: 99%
“…Over the entire 20 cm 2 surface area of a 5 cm diameter Si wafer, the variation (i.e., 1 standard deviation) in the thickness of 25 nm Al 2 O 3 films is 0.3 nm, despite the fact that the cumulative cross‐sectional area of the microcavities in the plasma array is only 2.5 cm 2 . From the viewpoint of electronic devices, perhaps the most important result is that films grown at 50°C and postannealed at 400°C have dielectric breakdown strengths of 6.1 MV/cm, [ 49 ] which lies within a factor of 2 of the highest values in the literature for Al 2 O 3 films grown at much higher temperatures. Because of the low substrate temperatures now accessible with MALD, electronic devices can be fabricated on flexible substrates such as PET.…”
Section: Mald Of Electronic and Photonic Filmsmentioning
confidence: 99%